Cracking the code of hatchery-based mass production of mola (Amblypharyngodon mola) seed for nutrition-sensitive aquaculture - Rajts, Francois; Dubey, Sourabh Kumar; Gogoi, Kalpajit; Das, Rashmi Ranjan; Biswal, Saurava Kumar; Padiyar, Arun Panemangalore; Rajendran, Suresh; Thilsted, Shakuntala Haraksingh; Mohan, Chadag Vishnumurthy; Belton, Ben (Frontiers in Aquaculture, 2023)
Small indigenous fish species (SIS) can be particularly rich in micronutrients and make a crucial contribution towards improving human nutrition. Introducing mola (Amblypharyngodon mola), an SIS particularly rich in vitamin A, into smallholder carp aquaculture systems has been widely promoted over the past decade as a promising nutritionsensitive innovation. However, standardized techniques for hatchery mass production of molado not yet exist. We hypothesized that lack of commercial hatchery mass-production techniques for mola seed is the key bottleneck limiting potential for widespread adoption of carp-SIS polyculture. To address this gap, we conducted breeding trials at a private hatchery in Odisha, India, from July-September 2022 to identify standardized methods for hatcherybased mass production of mola seed. Breeding was induced using Synthetic Gonadotropin Releasing Hormone analogue (SGnRHa) at 0.5 ml and 0.25 ml per kg body weight of females and males. Fish spawned in double hapas in breeding tanks. Fertilization rate, spawning rate and hatching rate over ten breeding cycles averaged 81%, 82%, and 85%, respectively. A total of 8.5 million fertilized eggs and 6.4 million hatchlings were produced. Survival of fry during larval rearing trials at a stocking rate of 500 hatchlings/m 2 was 58% after 22 days. Mola hatchlings and fry were sold to 29 farmers, at prices comparable to those of Indian Major Carp. This paper makes a unique contribution to the literature by documenting the entire process of hatchery based mola seed mass production, including brood collection and maintenance, hormone dose optimization, breeding arrangements, breeder characteristics, breeding behaviour and performance, fecundity, larval rearing, and seed sales to farmers. This information is intended to serve as a protocol to be followed by any individual or institution with an interest in mola breeding and makes an important contribution to the development of nutrition-sensitive aquaculture.